2016
DOI: 10.1111/vco.12277
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a PCR‐based lymphocyte clonality assay as a complementary tool for the diagnosis of feline lymphoma

Abstract: Differentiation between resident mature lymphocyte populations and small cell lymphoma cannot be made by cytological review alone and remains challenging in histopathological review. These cases warrant application of complementary tools like PCR-based immunoglobulin (IG) and T-cell receptor (TCR) clonality testing for confirmation. In this prospective study, diagnostic sensitivity and specificity of different primer sets for routine diagnosis of feline TCR gamma (TCRG) and complete IG heavy chain (IGH) gene r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 23 publications
1
32
0
Order By: Relevance
“…Additionally, we are designing IGL PARR primers to target other IGLV subgroups, which could increase the sensitivity of IGL PARR. The traditionally employed IGH‐VDJ assay only detected 50% of the B‐cell neoplasms in this study, which is within the range detected by some of the other publications assaying this region . This could be partly due to the types of samples selected; for example, if the B‐cell neoplasms sampled have a high degree of somatic hypermutation, primer annealing could be compromised.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…Additionally, we are designing IGL PARR primers to target other IGLV subgroups, which could increase the sensitivity of IGL PARR. The traditionally employed IGH‐VDJ assay only detected 50% of the B‐cell neoplasms in this study, which is within the range detected by some of the other publications assaying this region . This could be partly due to the types of samples selected; for example, if the B‐cell neoplasms sampled have a high degree of somatic hypermutation, primer annealing could be compromised.…”
Section: Discussionsupporting
confidence: 52%
“…The reported sensitivity for detecting a clonal TRG by PCR in T‐cell neoplasms has been relatively high, with 5/7 studies reporting sensitivities ≥79% . The sensitivity for detecting a clonal IGH receptor among feline B‐cell neoplasms has been historically lower, with sensitivity values ranging from 34% to 89% . One difficulty in detecting B‐cell neoplasms is that the IGH receptor can undergo somatic hypermutation, altering nucleotides at primer sites, which compromises primer binding.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Small cell GI LSA closely resembles feline inflammatory bowel disease (IBD) in its clinical presentation,2 with both diseases having poorly defined etiologies. Various risk factors including genetic and molecular alterations,3, 4, 5 diet,3, 6, 7 and chronic inflammation8, 9, 10 have been linked to the development of both disorders. Still other studies have suggested an association between chronic mucosal inflammation and the progression of IBD to pronounced dysplasia in the GI tract 11, 12, 13, 14…”
Section: Introductionmentioning
confidence: 99%
“…8 The sensitivity and specificity of clonality assays in human and veterinary medicine vary widely with sensitivities between 70.0 and 97.6% and specificities between 54.3-98.7%. 7,[9][10][11][12][13][14][15] These wide ranges are the result of a combination of technical and biological variability. 16 Because of the inherently high error rate for clonality assays, there are rigorous preanalytical, analytical, and postanalytical standards published in human medicine under the EuroClonality/BIOMED-2 clonality standardization group guidelines.…”
Section: Introductionmentioning
confidence: 99%